THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND ANTENATAL CARE COMPLIANCE AND K8 COVERAGE AT PMB ANA IMROATUS KLAKAH - Anggi Failla Kholina Madali; Widia Shofa Ilmiah (Yayasan Nuraini Ibrahim Mandiri, 2026)
Pregnancy is a period that is vulnerable to health problems. One effort to maintain maternal and fetal health is through antenatal care (ANC) examinations. Non-compliance with ANC visits can lead to decreased maternal health status and contribute to an increased maternal mortality rate. One of the factors influencing compliance with ANC visits is family support. Family support plays an important role in preventing high-risk pregnancies through the fulfillment of complete antenatal care visits, including K8 coverage. This study aimed to determine the relationship between family support and pregnant women’s compliance in undergoing antenatal care examinations to achieve K8 coverage at PMB Ana Imroatus. This study used an observational analytic design with a cross-sectional approach. The study population consisted of all pregnant women who underwent examinations at PMB Ana Imroatus, with a total sample of 31 respondents selected using total sampling technique. Data were analyzed using the Chi-Square test. The results showed that 51.6% of pregnant women received good family support and 61.3% were compliant with antenatal care examinations. The Chi-Square test results showed a p-value of 0.015 (p<0.05), indicating that there is a significant relationship between family support and pregnant women’s compliance in undergoing antenatal care examinations to achieve K8 coverage.